Photoredox-catalyzed silyldifluoromethylation of silyl enol ethers - Supranovich, Vyacheslav I.; Levin, Vitalij V.; Dilman, Alexander D. (Beilstein Journal of Organic Chemistry, 2020)
A method for the light-mediated fluoroalkylation of silyl enol ethers with (bromodifluoromethyl)trimethylsilane followed by a reduction of the primary products with sodium borohydride is described. An 18 W, 375 nm LED was used as the light source. The reaction is performed in the presence of a gold photocatalyst, which effects the generation of a (trimethylsilyl)difluoromethyl radical via cleavage of the carbon–bromine bond.
Keywords: difluoroalkylation; organofluorine compounds; photocatalysis; radical addition; silicon reagents